PROSPECTS FOR THE EXPORT OF AGRICULTURAL PRODUCTS FROM UKRAINE TO ASIAN COUNTRIES - PUGACHOV, Mykola; DUKHNYTSKYI , Bogdan (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article considers current state of Ukraine’s export of agri-food products to Asian countries, detailing its commodity and geographic structure. General socio-economic characteristics of the Asian region have been carried out. The main principles of the functioning of the agro-food sector in Asia in relation with its production and foreign trade are given. The largest exporters and importers of food among Asian countries have been determined according to the latest available data. Total agricultural trade of our country with China, India and Turkey highlighted. The dynamics of bilateral sectoral trade between partners and the key products of Ukrainian production supplied to their markets are considered. Further emphasis placed on the import needs of those food groups or commodity items by the specified countries, which Ukraine is already able to satisfy to a certain extent. An assessment of the impact of war and its negative consequences on the actual exports indicators from Ukraine to Asia during 2022-2023 was carried out. The importance of finding new sales markets and consolidating existing partner trade relations by concluding agreements on free trade was emphasized. It is pointed out the actual impossibility for our exporters to fully use the transport and logistics infrastructure, which affects the quantitative and qualitative indicators of foreign sales. In fact, against the background of the final decline in export revenues, the redirection of products from Asia to the markets of European Union does not have the proper effect and does not compensate for the losses incurred. Development prospects and opportunities for optimizing Ukrainian agri-food exports to Asian markets were given, taking into account the sector’s limited resources, short- and medium-term priorities of our industry producers, and existing requests of specific importing countries.